Sovereign wealth funds the new intersection of money and politics - Balding, Christopher (New York ; Oxford : Oxford University Press, 2012)
Establishing a political, economic, and historical framework to study sovereign wealth funds, this book provides the broadest and most detailed analysis to date.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Sovereign wealth funds; Investments, Foreign; International finance -- Case studies